Mikobiota pada Buah Pisang Kultivar Lampung untuk Pengendalian Hayati Fusarium semitectum - Okky Setyawati Dharmaputra; Lisdar Idwan Sudirman; Evarini Anna Ratnaningsih (Jurnal Fitopatologi Indonesia, 2018)
Fusarium semitectum is a pathogenic fungus causing fruit rot of banana fruits. Biological control agents have been used as an alternative to control postharvest diseases. The objective of this study was to test antagonistic potential of mycobiota of banana fruits (Musa cuminata cultivar Lampung) against F. semitectum BIO 91055. The tested fungi were isolated from healthy banana cultivar Lampung collected from Gembrong market located in Bogor using serial dilution method, followed by pour plate method. Test of antagonism activity was carried out using dual culture method. Seventeen fungal isolates were isolated, they consisted of 14 filamentous fungal isolates and 3 yeast isolates. Four filamentous fungal isolates inhibited the growth of F. semitectum BIO 91055 more than 70%, they were Aspergillus niger, Cercosporella sp., Plectosphaerella sp., and Trichoderma hamatum. Three isolates (Cercosporella sp., Plectosphaerella sp., and Trichoderma hamatum) did not cause any diseases of banana fruits and they were considered as potential biocontrol agents.